The influence of lateral beam profile modifications in scanned proton and carbon ion therapy: a Monte Carlo study - Parodi, Katia; Mairani, Andrea; Brons, Stephan; Naumann, J.; Krämer, M.; Sommerer, Florian; Haberer, Thomas (Physics in medicine and biology, 2010)
Scanned ion beam delivery promises superior flexibility and accuracy for highly conformal tumour therapy in comparison to the usage of passive beam shaping systems. The attainable precision demands correct overlapping of the pencil-like beams which build up the entire dose distribution in the treatment field. In particular, improper dose application due to deviations of the lateral beam profiles from the nominal planning conditions must be prevented via appropriate beam monitoring in the beamline, prior to the entrance in the patient. To assess the necessary tolerance thresholds of the beam monitoring system at the Heidelberg Ion Beam Therapy Center, Germany, this study has investigated several worst-case scenarios for a sensitive treatment plan, namely scanned proton and carbon ion delivery to a small target volume at a shallow depth. Deviations from the nominal lateral beam profiles were simulated, which may occur because of misaligned elements or changes of the beam optic in the beamline. Data have been analysed with respect to the lateral penumbra, homogeneity and coverage of the dose deposition in the target volume. The results indicate that homogeneity is not seriously compromised by extremely narrow profiles for the standard planning choices of the lateral raster scan stepping and dose grid. Differently, broad beam distributions can significantly deteriorate the conformality of the dose delivery and too large increases (above ≈150-200% of the nominal spotsize) must be prevented.
Gesehen am 26.06.2023